Cool and hot executive functions at 5 years old as predictors of physical and relational aggression between 5 and 6 years old. (March 2019) - O'Toole, Sarah E.; Tsermentseli, Stella; Humayun, Sajid; Monks, Claire P.
To study the role of executive function (EF) in the early development of aggression, the role of cool and hot EF skills at 5 years old, in the development of physical and relational aggression between 5 and 6 years old, was explored. Typically developing children ( N = 80) completed tasks assessing their cool (inhibition, working memory, planning) and hot EF (affective decision making, delay of gratification) skills at 5 years old. Longitudinal data were collected from teachers that rated children's aggression when they were 5, 5.5, and 6 years old. Inhibition at 5 years old predicted changes in physical and relational aggression between 5 and 6 years old. Early cool EF, but not hot EF, may therefore be associated with aggression and inhibitory control specifically with changes in aggression during early childhood.